Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/ijerph17082965
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Traffic-Related Particulate Matter 2.5 Triggers Th2-Dominant Ocular Immune Response in a Murine Model

Abstract: Ambient particulate matter (PM), a major component of air pollution, aggravates ocular discomfort and inflammation, similarly to dry eye disease (DED) or allergies. However, the mechanism(s) by which PM induces the ocular inflammatory response is unknown. This study investigated the immunological response of traffic-related fine particulate matter (PM2.5) on the ocular surface in a murine model. C57BL/6 mice were exposed by topical application to PM2.5 or vehicle for 14 days to induce experimental environmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 49 publications
4
16
0
Order By: Relevance
“…Furthermore, the skin prick test response to Asian dust has been found to correlate with the mean wheal diameters for pollens and fungi, implying its adjuvant effect [18]. Although the mechanistic studies on the effect of particulate air pollutants on the ocular surface are relatively limited [19][20][21][22][23], their biological and immunomodulatory effects on the airways have been extensively studied [24]. However, since the lower respiratory tract is accessible to only small particles with a median aerodynamic diameter under 2.5 μm, the effect of larger particles such as pollen grains onto the mucosal surface has been less characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the skin prick test response to Asian dust has been found to correlate with the mean wheal diameters for pollens and fungi, implying its adjuvant effect [18]. Although the mechanistic studies on the effect of particulate air pollutants on the ocular surface are relatively limited [19][20][21][22][23], their biological and immunomodulatory effects on the airways have been extensively studied [24]. However, since the lower respiratory tract is accessible to only small particles with a median aerodynamic diameter under 2.5 μm, the effect of larger particles such as pollen grains onto the mucosal surface has been less characterized.…”
Section: Introductionmentioning
confidence: 99%
“…PM 2.5 has also been found to induce mast cells and eosinophilic cells infiltration into the conjunctiva in a murine model. The mast cell is known as a key immune-regulatory factor in the Th2-mediated responses, indicating PM 2.5 might trigger Th2-dominant ocular immune response 18 . In a study conducted in Tokyo, elevated level of atmosphere PM 2.5 was found to be considerably associated with an increase in numbers of outpatient visits ( r = 0.62, p = 0.018) for AC from May to July, while there seems to be no statistical significance of correlation from August to November, indicating that PM 2.5 may have played a role in AC development during the nonpollen season 19 .…”
Section: Discussionmentioning
confidence: 99%
“…IL-17 induces the secretion of pro-inflammatory cytokines such as IL-1, IL-6 and TNF-α, and these cytokines are upregulated in DED [ 50 ]. Lee et al [ 51 ] suggested that the topical application of PM 2.5 elevated dendritic cell maturation and the expression of TNF-α, IL-1β and IL-6 in a murine model. Hyun et al [ 52 ] also reported that the expression of TNF-α and IL-6 was increased in the PM 2.5 -induced DED rat model, but extract of apricot kernel, the seed of Prunus armeniaca L. (Prunus, apricot), had a protective effect against DED by PM 2.5 .…”
Section: Discussionmentioning
confidence: 99%